PENGEMBANGAN DAN IMPLEMENTASI MEDIA POP UP BOOK BERBASIS POWERPOINT BERMUATAN SEX EDUCATION DALAM PEMBELAJARAN BAHASA INGGRIS DI SD - Riesma Aulia Salsabila; Aulia Zahra Ihsani; Rif’an Fazrin Zulfikar; Rafi Nurfadly; Indra Komara; Winti Ananthia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Cases of child sexual abuse often occur in Indonesia, so it’s important to educate children from an early age so that they can understand the forms of sexual acts and how to prevent them. In addition, the English language skills of elementary school students are also a concern because students still experience delays in understanding the material and vocabulary. This problem can be solved by integrating sex education and English learning through PowerPoint-based pop up book media in English with sex education content, named WiseBook: Wisdom in Sexual Education E-Book. This research aims to obtain an overview of the process, feasibility test data and application test data on WiseBook media development. The research method employed is D&D with the results of the applied research based on the results of the material expert test which obtained a score of 65 out of 75 resulting in a percentage of 86% in the “very good” category and the media expert test obtained a score of 56 out of 75 resulting in a percentage of 74.6% in the “good” category. Based on the results of implementation and interviews with teachers, it shows that the use of WiseBook media can be applied to low-grade elementary school students because students become active and interactive during learning. The application of this learning media can make it easier for students to remember and understand the material presented, especially in learning English which is often considered difficult. Kasus kekerasan seksual pada anak sering terjadi di Indonesia, sehingga penting untuk memberikan edukasi pada anak sejak usia dini agar mereka dapat memahami bentuk tindakan seksual dan cara mencegahnya. Selain itu, kemampuan berbahasa Inggris siswa sekolah dasar juga menjadi perhatian karena siswa masih mengalami keterlambatan dalam memahami materi dan kosakata. Permasalahan ini dapat diatasi dengan mengintegrasikan sex education dan pembelajaran Bahasa Inggris melalui media pop up book berbasis PowerPoint berbahasa Inggris bermuatan sex education, yang diberi nama WiseBook: Wisdom in Sexual Education E-Book. Riset ini bertujuan untuk memperoleh gambaran proses, data hasil uji kelayakan dan data hasil uji penerapan pada pengembangan media WiseBook. Metode riset yang digunakan yaitu D&D dengan hasil riset yang diterapkan berdasarkan hasil uji ahli materi yang memperoleh skor 65 dari 75 menghasilkan persentase 86% dengan kategori “sangat baik” dan uji ahli media memperoleh skor 56 dari 75 menghasilkan persentase 74,6% dengan kategori “baik”. Berdasarkan hasil implementasi dan wawancara pada guru, menunjukkan bahwa penggunaan media WiseBook dapat diterapkan kepada siswa sekolah dasar kelas rendah karena siswa menjadi aktif dan interaktif selama pembelajaran berlangsung. Dengan diterapkannya media pembelajaran ini dapat mempermudah siswa untuk mengingat dan memahami materi yang disampaikan, terutama dalam pembelajaran Bahasa Inggris yang seringkali dianggap sulit.